A ANÁLISE DA VULNERABILIDADE À SALINIZAÇÃO DAS ÁGUAS SUBTERRÂNEAS DA ILHA DE SÃO LUÍS: Estudo de caso na área Itaquí - Bacanga - Soares, Luis Alfredo Lopes (2004)
The salinization vulnerability of groundwater in the Itaquí-Bacanga area, caused by the super exploitation in the coastal aquifers usually creates the phenomenon of seawater intrusion, justified by the increasing of the freshwater/ seawater interface, which can bring a scenario of general contamination. Instead of using traditional methods for contamination evaluation, which are not applicable in this case, different methods must be applied using much more complex knowledges about hydrogeology and hydrochemistry that demand more tools for collecting hydrogeochemistry parameters. In the northwest coast of the island of São Luís, Itaquí-Bacanga area, some zones in the aquifer system are already seriously damaged by reasons explained above, causing deactivation of some wells through salinization. From the analysis of lithologic profiles, physicochemical parameters and integrating geotopographics and chemical datas, a vulnerability map was built, also considering historical features.